PENGARUH KESEJAHTERAAN, LINGKUNGAN KERJA DAN PEMBERIAN INSENTIF TERHADAP KEPUASAN KERJA KARYAWAN ASTRIDO TOYOTA PONDOK INDAH - Diah Sulistyawati; Riduan Siagian (Jurnal Ekonomi Bisnis Indonesia, 2021)
Abstract: The purpose of this study was to determine the influence of welfare, job environment, and provision of incentives on job satisfaction partially and simultaneously. Casual research methods. The sample in this study was PT Astrido Toyota Pondok Indah, South Jakarta with 60 respondents. The data used are primary data. The data collection method uses a questionnaire. Analysis of the data used id quantitative using SPSS versions 23. The results of this study partially indicate that welfare has a signidicant effect on job satisfaction, the job environment does not have a significant effect on job satisfaction, and the provision of incentives has a significant effect on job satisfaction. While simultaneously welfare, job environment and the provision of incentives together have significant and positive effect.